Gastric perforation resulting into pneumoperitoneum in a neonate: a case report. Issue 8 (26th August 2020) - Lodhia, Jay; Msuya, David; Philemon, Rune; Sadiq, Adnan; Mremi, Alex
Abstract: Gastric perforation in a neonate is a rare surgical emergency in routine practice. The causes and predisposing factors for gastric perforation in a neonate vary from traumatic to benign conditions like inflammatory processes. Early detection, intensive care, stabilization and prompt surgery yield positive outcome. Early diagnosis is important for better prognosis. Simple investigation such as plain abdominal X-ray can adequately lead to the diagnosis by showing pneumoperinoneum. We present a 3-day-old neonate; born at term who presented with abdominal distension and vomiting. Plain abdominal X-ray revealed pneumoperitoneum. Emergency laparotomy was performed where a gastric perforation was found measuring 0.5 by 0.5 cm located on the anterior aspect of the stomach body near the pylorus. The baby underwent successful surgical intervention and recovered well.